2021
DOI: 10.2147/rrtm.s306001
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Infection is High at Transit and Destination Phases Among Seasonal Migrant Workers in Development Corridors of Northwest Ethiopia: A Repeated Cross-Sectional Study

Abstract: Purpose: Malaria is a leading public health problem in Ethiopia. Every year, thousands of seasonal farm workers travel to farm corridors in Northwest Ethiopia and fall at risk of malaria infection. However, the magnitude of malaria infection and risk factors during harvest time were not well identified. This study aimed at estimating the prevalence and risk factors of malaria infection among seasonal migrant workers in Northwest Ethiopia. Methods: A repeated cross-sectional study was conducted at transit and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(109 reference statements)
0
0
0
Order By: Relevance
“…The substantial number of COVID-19 infections (22.3%) among migrants found could be attributed to the province's host of large migrant communities. Substandard socioeconomic conditions of migrants have been determined to be associated with a high incidence of communicable diseases such as diphtheria, pulmonary tuberculosis, malaria, syphilis, cholera, leprosy, and lymphatic filariasis in many countries [50][51][52][53][54]. On the current pandemic, various studies have reported similar findings of high recorded COVID-19 cases in migrant communities [10,55,56].…”
Section: Migrants and Vulnerabilities To Covid-19mentioning
confidence: 93%
“…The substantial number of COVID-19 infections (22.3%) among migrants found could be attributed to the province's host of large migrant communities. Substandard socioeconomic conditions of migrants have been determined to be associated with a high incidence of communicable diseases such as diphtheria, pulmonary tuberculosis, malaria, syphilis, cholera, leprosy, and lymphatic filariasis in many countries [50][51][52][53][54]. On the current pandemic, various studies have reported similar findings of high recorded COVID-19 cases in migrant communities [10,55,56].…”
Section: Migrants and Vulnerabilities To Covid-19mentioning
confidence: 93%